2015
DOI: 10.1200/jco.2015.61.4578
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Phase II Study of Ruxolitinib or Placebo in Combination With Capecitabine in Patients With Metastatic Pancreatic Cancer for Whom Therapy With Gemcitabine Has Failed

Abstract: Purpose Patients with advanced pancreatic adenocarcinoma have a poor prognosis and limited second-line treatment options. Evidence suggests a role for the Janus kinase (JAK)/signal transducer and activator of transcription pathway in the pathogenesis and clinical course of pancreatic cancer. Patients and Methods In this double-blind, phase II study, patients with metastatic pancreatic cancer who had experienced treatment failure with gemcitabine were randomly assigned 1:1 to the JAK1/JAK2 inhibitor ruxolitinib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
164
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(170 citation statements)
references
References 60 publications
4
164
1
1
Order By: Relevance
“…Secondly, it would support the hypothesis that routine markers of the systemic inflammatory response, and in particular the mGPS, may aid in the identification and selection of patients likely to benefit from such targeted therapies (50). In keeping with such a scheme, one recent clinical trial of a JAK inhibitor in patients with metastatic pancreatic cancer found an increase in overall survival only in those patients with an elevated CRP or mGPS (51). Therefore, it is clear that markers of the host inflammatory response should be incorporated into future studies of agents targeting the IL-6/JAK/STAT3 pathway in cancer.…”
Section: P=0039)mentioning
confidence: 80%
“…Secondly, it would support the hypothesis that routine markers of the systemic inflammatory response, and in particular the mGPS, may aid in the identification and selection of patients likely to benefit from such targeted therapies (50). In keeping with such a scheme, one recent clinical trial of a JAK inhibitor in patients with metastatic pancreatic cancer found an increase in overall survival only in those patients with an elevated CRP or mGPS (51). Therefore, it is clear that markers of the host inflammatory response should be incorporated into future studies of agents targeting the IL-6/JAK/STAT3 pathway in cancer.…”
Section: P=0039)mentioning
confidence: 80%
“…The fact that therapies with a broader mechanism of action will become available for research projects in the near future is equally important. In addition to the omnipresent immunotherapy, stromal depletion, e.g., with hyaluronidase [55] and anti-inflammatory concepts [56] , appear most promising.…”
Section: Resultsmentioning
confidence: 99%
“…In preclinical pancreatic cancer models, the JAK/STAT and related inflammatory pathways were found to drive cancer progression. Ruxolitinib is a JAK 1/2 inhibitor which has been evaluated in refractory pancreatic cancer with or without capecitabine in a randomized phase II study (65). In a pre-specified subgroup of patients with systemic inflammation as measured by elevated serum C-reactive protein (CRP >13 mg/L), survival significantly favored the ruxolitinib arm (3 and 6 months survivals of 48% and 42% vs. 29% and 11%, respectively).…”
Section: Janus Kinase (Jak) 1/2mentioning
confidence: 99%